Quality of life, socioeconomic and psychological concerns in parents of children with tuberous sclerosis complex, STXBP1 and SYNGAP1 encephalopathies: a mixed method study - Salcedo-Perez-Juana, María; Palacios-Ceña, Domingo; San-Martín-Gómez, Ana; Aledo-Serrano, Ángel; Florencio, Lidiane Lima (Frontiers in Pediatrics, 2023)
Developmental and Epileptic Encephalopathies (DEEs) occur in childhood and are associated with severe epileptic seizures and neurological impairment. The aim of this study was to combine quantitative and qualitative methodologies to comprehensively describe factors related to quality of life, impact on the family and psychosocial factors in parents of children with TSC, STXBP1 and SYNGAP1 variants. A convergent parallel mixed design including parents of children with DEE. In the cross-sectional study, 20 parents (10STXBP1, five SYNGAP1, five TSC) were given questionnaires on quality of life, impact on the family and psychological factors. In the descriptive qualitative study, in-depth interviews were conducted with 18 parents (nine STXBP1, five TSC, four SYNGAP1) using a semi-structured questionnaire. A thematic analysis was carried out. The results of the two studies were combined by showing similarities and differences through tables, figures, accounts, and joint displays. In terms of quality of life, the integrated results were consistent in highlighting the importance of family interaction, although in the qualitative section the influence of the relationship between the children's siblings, the relationship with health professionals and the difficulties in obtaining public aid were highlighted. In terms of impact, the integrated results show that the illness has a significant impact on the family; the financial burden is highlighted, and the experience of the illness is discussed in depth. Finally, the psychological aspects, symptoms such as anxiety, stress and strain, were consistent. Most of the participants reported sleep disturbance, as identified in the questionnaire, although not mentioned in the interviews. The combined results of the mixed method provide an in-depth analysis of the impact of DEEs on parents of children with STXBP1, SYNGAP1 and TSC.